Preliminary Study on Wind Turbines for Power on Floating Net Cages - Herlina; Agustina, Sri; Sariman; Pratama, M. Akbar; Azhary, M. Ichsan (Fakultas Teknik Universitas Pancasila, 2024)
Focus of this primary study is to investigate how efficient horizontal-axis wind turbines (HAWT) and vertical-axis wind turbines (VAWT) are in preserving floating net cages. The expansion of the aquaculture sector, which is increasingly dependent on advanced technologies like monitoring and data processing systems in open waters, need a reliable energy source. The investigation was carried out by manipulating wind speed, battery charging duration, and electrical load for both types of wind turbines in simulated field circumstances. Based on the test results, HAWT outperforms VAWT in generating a greater battery voltage and achieving a more consistent charging period at the same wind speed. The smallest voltage rise in HAWT is 2.2 m/s with a 5-minute 0% charging time and the maximum is 1.2 m/s with a 15-minute 38.1% charging time. While the VAWT demonstrates better stability under specific load conditions, the HAWT can generate substantial power throughout a wide range of wind speeds. This renders HAWT more appropriate for utilization in dynamic maritime applications, such as floating net cages.